2023
DOI: 10.52082/jssm.2023.51
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Pectoralis Major Foam Ball Rolling on Shoulder Extension Range of Motion, Isometric Contraction Torque, and Muscle Stiffness

Abstract: Although it is well known that foam rolling (FR) of the lower extremities can increase the range of motion (ROM) of a joint while likely having no detrimental effect on muscle performance, to date, this is not clear if this is the case for the upper body. Therefore, the purpose of this study was to analyze the effects of a 2-min FR intervention of the pectoralis major (PMa) muscle on muscle stiffness of the PMa, shoulder extension ROM, and maximal voluntary isometric contraction (MVIC) peak torque. Thirty-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The meta-analytical approaches might be seen as a supplementation to quantify results. Although some short duration stretching interventions sufficiently increased maximal strength (Nelson et al, 2012;Mizuno 2019), consistent stretchinduced strength and muscle size increases were reported after longer stretching durations (≥10 min per session) (Chen et al, 2011;Wohlann et al, 2023;Wohlann et al, 2024, Warneke et al, 2022a, Reiner et al, 2023Warneke et al, 2022). However, stretching durations of the included studies primarily used short stretching durations of a few minutes.…”
Section: Limitationsmentioning
confidence: 87%
“…The meta-analytical approaches might be seen as a supplementation to quantify results. Although some short duration stretching interventions sufficiently increased maximal strength (Nelson et al, 2012;Mizuno 2019), consistent stretchinduced strength and muscle size increases were reported after longer stretching durations (≥10 min per session) (Chen et al, 2011;Wohlann et al, 2023;Wohlann et al, 2024, Warneke et al, 2022a, Reiner et al, 2023Warneke et al, 2022). However, stretching durations of the included studies primarily used short stretching durations of a few minutes.…”
Section: Limitationsmentioning
confidence: 87%
“…The results showed no significant change in ankle ROM following the upper body stretch program. Indeed, the applied stretching stimulus of the pectoralis muscles is enough to induce local changes in ROM (i.e., shoulder extension) as have been shown in a previous study (Reiner et al., 2023).…”
Section: Discussionmentioning
confidence: 55%
“…Szymczyk et al [ 42 ] observed a marginal decrease in Achilles tendon stiffness after a one-minute percussive massage, but this was not statistically significant ( p = 0.073). Further, a brief foam rolling session on the pectoralis major muscle did not alter its stiffness [ 43 ]. Yet, 5 min of classical massage and 7 min of warm-up sports massage did decrease the stiffness in the medial gastrocnemius [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%